Manufacturing method of cathode active material

JP2025022345AActive Publication Date: 2025-02-14PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023126808
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-02-14
Estimated Expiration
2043-08-03

AI Technical Summary

Benefits of technology

【0008】 上述の通り、一般的な正極活物質の製造では、遷移金属の硫酸塩(NiSO4、CoSO4、MnSO4など)を出発原料として使用している。このため、製造後の正極活物質に、硫酸ナトリウム(Na2SO4)などの硫酸塩が混入することがある。そして、本発明者の検討の結果、正極活物質中の硫酸塩の混入量が増大すると、リチウムイオン二次電池の初期抵抗が増加することが分かった。ここに開示される製造方法は、かかる知見に基づいたものである。具体的には、ここに開示される製造方法は、前駆体生成工程を実施する前の遷移金属溶液の硫酸イオン(SO42-)の濃度を0.9mol/L以下にする。これによって、製造後の正極活物質への硫酸塩の混入量を低減できるため、リチウムイオン二次電池の初期抵抗の低減に貢献することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022345000001_ABST
    Figure 2025022345000001_ABST
Patent Text Reader

Abstract

To provide a method of manufacturing a cathode active material capable of contributing to improvement of battery performance.SOLUTION: A manufacturing method includes: a preparation step S10 of preparing a starting material containing at least a transition metal element; a preparation step S20 of preparing a transition metal solution by dissolving the transition metal element in the starting material into an extraction liquid; a precursor generation step S30 of crystallizing a cathode active material precursor by adding an alkaline solution to the transition metal solution; and an active material generation step S40 of generating a cathode active material by heating the cathode active material precursor together with a lithium compound. In the manufacturing method, a sulfate ion concentration of the transition metal solution in implementing the precursor generation step is made equal to or less than 0.9 mol / L.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing a positive electrode active material. Specifically, the present disclosure relates to a method for producing a positive electrode active material for a lithium ion secondary battery. [Background technology]

[0002] Lithium ion secondary batteries are widely used in various devices such as mobile terminals and vehicles. For example, lithium transition metal composite oxides are used as the positive electrode active material of these lithium ion secondary batteries. Examples of transition metals contained in these lithium transition metal composite oxides include Ni, Co, and Mn.

[0003] Patent Document 1 discloses an example of a precursor of this type of positive electrode active material (lithium transition metal composite oxide). As described in Patent Document 1, in the production of a positive electrode active material, a transition metal sulfate (NiSO4, CoSO4, MnSO4, etc.) is usually prepared as a starting material. Next, this sulfate is dissolved in water to prepare a mixed aqueous solution (transition metal solution). Then, an alkaline solution (NaOH, etc.) is added to this transition metal solution. This causes a compound containing a transition metal (positive electrode active material precursor) to precipitate. Then, this positive electrode active material precursor is mixed with a lithium compound and baked. This allows the production of a lithium transition metal composite oxide. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2018 / 123995 Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, there has been an increasing demand for improved performance of lithium ion secondary batteries. The technology disclosed herein has been made in response to such demand, and aims to provide a method for producing a positive electrode active material that can contribute to improving battery performance. [Means for solving the problem]

[0006] In order to solve the above problems, a method for producing a positive electrode active material (hereinafter, also simply referred to as a "production method") having the following configuration is provided.

[0007] The method for producing a positive electrode active material disclosed herein includes a preparation step of preparing a starting material containing at least a transition metal element, a preparation step of preparing a transition metal solution by dissolving the transition metal element in the starting material in an extract, a precursor production step of crystallizing a positive electrode active material precursor by adding an alkaline solution to the transition metal solution, and an active material production step of producing a positive electrode active material by heating the positive electrode active material precursor together with a lithium compound. The production method disclosed herein is characterized in that the sulfate ion concentration of the transition metal solution during the precursor production step is 0.9 mol / L or less.

[0008] As described above, in the production of typical positive electrode active materials, sulfates of transition metals (such as NiSO4, CoSO4, and MnSO4) are used as starting materials. For this reason, sulfates such as sodium sulfate (Na2SO4) may be mixed into the produced positive electrode active material. As a result of the inventor's investigation, it was found that an increase in the amount of sulfates mixed into the positive electrode active material increases the initial resistance of the lithium ion secondary battery. The production method disclosed herein is based on this knowledge. Specifically, the production method disclosed herein involves removing sulfate ions (SO4 2- ) to 0.9 mol / L or less. This reduces the amount of sulfate mixed into the positive electrode active material after production, which contributes to reducing the initial resistance of lithium-ion secondary batteries. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a flowchart illustrating the method for producing a positive electrode active material according to the first embodiment. [Diagram 2] FIG. 2 is a flow chart illustrating a preparation process in another embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments of the technology disclosed herein will be described with reference to the drawings. Matters other than those specifically mentioned in this specification and necessary for implementing the technology disclosed herein can be understood as design matters for a person skilled in the art based on the prior art in the field. The technology disclosed herein can be implemented based on the contents disclosed in this specification and the technical common sense in the field. In addition, the expression "A to B" indicating a range in this specification includes the meaning of "A or more and B or less," as well as "preferably greater than A" and "preferably smaller than B."

[0011] <First embodiment> Hereinafter, a first embodiment of the manufacturing method disclosed herein will be described. In the following, the cathode active material to be manufactured will be described, and then the specific steps of the manufacturing method according to this embodiment will be described.

[0012] [Cathode active material] In the manufacturing method according to the present embodiment, a lithium transition metal composite oxide to be used as a positive electrode active material of a lithium ion secondary battery is manufactured. The lithium transition metal composite oxide is an oxide containing lithium (Li) and a transition metal element. Examples of the transition metal element include nickel (Ni), cobalt (Co), and manganese (Mn). Specific examples of the lithium transition metal composite oxide include lithium nickel composite oxide (LN oxide), lithium cobalt composite oxide (LC oxide), lithium nickel manganese composite oxide (LNM oxide), lithium manganese cobalt composite oxide (LMC oxide), lithium nickel cobalt composite oxide (LNC oxide), and lithium nickel cobalt manganese composite oxide (LNCM oxide). Note that these lithium transition metal composite oxides may contain elements (additive elements) other than Li and the transition metal element. These additional elements include Mg, Ca, Al, Ti, V, Cr, Si, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Fe, Zn, Sn, B, C, Si, P, S, F, Cl, Br, I, etc.

[0013] Although the details will be described later, the manufacturing method according to this embodiment can reduce the amount of sulfates mixed into the positive electrode active material after manufacturing. Specifically, the manufacturing method according to this embodiment can reduce the amount of sulfur ions (SO4 2- The content of sulfur ions (SO4) can be reduced to 1.2 wt% or less (preferably 0.9 wt% or less, more preferably 0.6 wt% or less, and particularly preferably 0.3 wt% or less). This can reduce the initial resistance of the lithium ion secondary battery. 2- The "content of sulfur (SO4)" is a value calculated based on the measurement results of high-frequency inductively coupled plasma (ICP). Specifically, the weight (wt%) of elemental sulfur (S) in the positive electrode active material can be measured using ICP. 2- ) the content of sulfur ions can be calculated based on the weight of the above elemental sulfur.

[0014] [Method of manufacturing battery materials] Next, a method for producing a positive electrode active material according to this embodiment will be described below. Fig. 1 is a flow chart illustrating a method for producing a positive electrode active material according to this embodiment.

[0015] 1, the method for producing a battery material according to this embodiment includes a preparation step S10, a preparation step S20, a precursor production step S30, and an active material production step S40. Each step will be described below using an example of producing an LNCM oxide as a positive electrode active material.

[0016] (1) Preparation process S10 In the preparation step S10, starting materials containing at least transition metal elements are prepared. Although details will be described later, the starting materials can be appropriately selected from conventionally known materials according to the composition of the production target (positive electrode active material). For example, in this embodiment, an LNCM oxide containing Ni, Co, and Mn as transition metal elements is produced. In this case, in this step, starting materials containing Ni, Co, and Mn are prepared. Note that the type of starting materials prepared in this step may be one type or multiple types. Specifically, one type of starting material that can supply all of the necessary transition metal elements may be prepared. Also, multiple types of starting materials may be prepared, and the necessary transition metal elements may be supplied by combining the multiple types of starting materials. For example, in this embodiment, a starting material containing Ni and Co (NiCo source) and a starting material containing Mn (Mn source) are separately prepared. This makes it possible to supply Ni, Co, and Mn required for the production of the LNCM oxide. Note that the NiCo source in this embodiment is obtained by sintering the positive electrode active material (LNCM oxide) of a used lithium ion secondary battery. On the other hand, manganese chloride (MnCl2) is used as the Mn source.

[0017] (2) Preparation process S20 In the preparation step S20, a transition metal solution is prepared by dissolving the transition metal elements in the starting material in an extract. This step can be performed without any particular limitation as long as a transition metal solution containing a desired transition metal element can be prepared, and any conventionally known procedure can be adopted. In this embodiment, first, the NiCo raw material (calcined LNCM oxide) is immersed in ammonia water. As a result, nickel oxide (NiO) and cobalt oxide (CoO) in the calcined LNCM oxide are leached into the ammonia water. This makes it possible to obtain a solution containing Ni and Co elements (NiCo solution). On the other hand, manganese oxide (MnO) in the calcined LNCM oxide is difficult to leach into the ammonia water. Therefore, in this embodiment, manganese chloride is separately prepared as a Mn source. Then, this manganese chloride is dissolved in another extract (such as water), so that a solution containing Mn element (Mn solution) can be prepared. Then, this Mn solution is added to the NiCo solution, so that a transition metal solution containing Ni, Co, and Mn (NiCoMn solution) can be prepared.

[0018] The metal concentration of the transition metal solution is preferably 1.0 mol / L or more, more preferably 1.2 mol / L or more, even more preferably 1.4 mol / L or more, and particularly preferably 1.5 mol / L or more. This allows efficient crystallization of the positive electrode active material precursor in the precursor generation step S30. On the other hand, if the metal concentration of the transition metal solution becomes too high, it approaches the saturation solubility, and there is a risk that the metal will precipitate with a slight temperature change. From this viewpoint, the metal concentration of the transition metal solution is preferably 2.6 mol / L or less, more preferably 2.4 mol / L or less, even more preferably 2.2 mol / L or less, and particularly preferably 2 mol / L or less. The mixing ratio of the transition metal elements (Ni, Co, Mn, etc.) in the transition metal solution is appropriately adjusted according to the composition of the positive electrode active material to be manufactured.

[0019] In this step, a reducing agent and a pH buffer may be added to the extraction solution. This allows Ni and Co elements to be extracted more easily. As the reducing agent, hydrogen peroxide solution or the like can be preferably used. As the pH buffer, ammonium sulfate or the like can be preferably used. When ammonium sulfate is used as the pH buffer, it is preferable to adjust the amount of the pH buffer added so that the sulfate ion concentration of the transition metal solution is 0.9 mol / L or less, as described below.

[0020] (3) Precursor generation step S30 In the precursor generation step S30, an alkaline solution is added to the transition metal solution to crystallize a positive electrode active material precursor. In this step, as long as a positive electrode active material precursor can be generated, a conventionally known crystallization process can be adopted without any particular restrictions. Examples of the alkaline solution include an aqueous ammonia (NH3) solution, an aqueous sodium hydroxide (NaOH) solution, and an aqueous potassium hydroxide (KOH) solution. In this embodiment, an aqueous NaOH solution is added to the above-mentioned transition metal solution (NiCoMn solution) to control the pH of the transition metal solution to be strongly alkaline (pH = 11 or more). As a result, NiCoMn hydroxide is crystallized in the transition metal solution. This NiCoMn hydroxide can be collected by using solid-liquid separation. Then, the collected NiCoMn hydroxide is washed with water or the like and then dried. As a result, a dried NiCoMn hydroxide (positive electrode active material precursor) is obtained.

[0021] (4) Active material generation step S40 In the active material production step S40, the positive electrode active material precursor is heated together with a lithium compound to produce a positive electrode active material. In this embodiment, the positive electrode active material precursor (NiCoMn hydroxide) is mixed with a lithium compound (Li2CO3, LiOH, etc.). The mixing ratio here is appropriately adjusted depending on the composition of the positive electrode active material to be produced. Then, this mixture is fired under an oxygen atmosphere. In this way, a positive electrode active material (LNCM oxide) for a lithium ion secondary battery can be produced.

[0022] The maximum temperature in the calcination process is preferably 700°C or higher, more preferably 725°C or higher, even more preferably 750°C or higher, and particularly preferably 775°C or higher. This allows the positive electrode active material precursor and the lithium compound to react appropriately, and the positive electrode active material precursor can be efficiently produced. On the other hand, if the maximum temperature is too high, it may cause a decrease in battery characteristics due to excessive crystal growth. From this viewpoint, the maximum temperature in the calcination process is preferably 900°C or lower, more preferably 875°C or lower, even more preferably 850°C or lower, and particularly preferably 825°C or lower. In addition, the calcination time is preferably 3 hours or more, more preferably 3.5 hours or more, even more preferably 4 hours or more, and particularly preferably 4.5 hours or more. This allows the positive electrode active material precursor and the lithium compound to react sufficiently. On the other hand, the upper limit of the calcination time is not particularly limited, and may be 7 hours or less, 6.5 hours or less, 6 hours or less, or 5.5 hours or less. In this specification, the term "firing time" refers to the time during which the maximum temperature is maintained.

[0023] (5) Sulfate ion control The manufacturing method disclosed herein is characterized in that the sulfate ion concentration of the transition metal solution during the precursor generation step is set to 0.9 mol / L or less. According to experiments conducted by the present inventors, it has been confirmed that the use of such a transition metal solution with a low sulfate ion concentration can reduce the amount of sulfates mixed into the positive electrode active material after production. Furthermore, the use of this positive electrode active material can reduce the initial resistance of the lithium ion secondary battery.

[0024] Here, in the manufacturing method according to the first embodiment, starting materials that do not substantially contain sulfur elements are used. This allows the sulfate ion concentration of the transition metal solution to be controlled to 0.9 mol / L or less. Specifically, in this embodiment, a used positive electrode active material (LNCM oxide) is used as the NiCo source. This used positive electrode active material does not substantially contain sulfur elements, unlike nickel sulfate (NiSO4) which is a conventional Ni source, or cobalt sulfate (CoSO4) which is a conventional Co source. In addition, manganese chloride used as the Mn source also does not substantially contain sulfur elements, unlike manganese sulfate (MnSO4) which is a conventional Mn source. By using these starting materials, it is possible to prevent the inclusion of sulfur elements derived from the starting materials. This allows the sulfate ion concentration of the transition metal solution to be controlled to 0.9 mol / L or less. And, by using this transition metal solution, the amount of sulfates (such as Na2SO4) precipitated in the precursor generating step S30 can be significantly reduced. As a result, the amount of sulfate mixed into the positive electrode active material after production can be reduced, and the performance (initial resistance) of the lithium ion secondary battery can be improved.

[0025] In this specification, "using starting materials that are substantially free of sulfur element" refers to not intentionally using compounds containing sulfur element as starting materials. Therefore, when a trace amount of sulfur element is inevitably mixed into the starting materials due to the manufacturing process or the like, it is interpreted as "using starting materials that are substantially free of sulfur element". For example, when the content of sulfur element relative to the total weight (100wt%) of the starting materials is 1wt% or less (preferably 0.1wt% or less, more preferably 0.01wt% or less, even more preferably 0.001wt% or less, and particularly preferably 0.0001wt% or less), it can be said that "using starting materials that are substantially free of sulfur element". By using such starting materials, a transition metal solution with a sulfate ion concentration of 0.9mol / L or less can be easily prepared.

[0026] The sulfate ion concentration of the transition metal solution is preferably 0.8 mol / L or less, more preferably 0.7 mol / L or less, even more preferably 0.6 mol / L or less, and particularly preferably 0.5 mol / L or less. As the sulfate ion concentration of the transition metal solution decreases, the amount of sulfate salts mixed into the positive electrode active material decreases, so that a positive electrode active material with higher performance can be produced. On the other hand, the lower limit of the sulfate ion concentration of the transition metal solution is not particularly limited, and may be 0 mol / L (no sulfate ions at all).

[0027] In addition, the total amount of transition metal elements in the transition metal solution (M T ) and the amount of sulfur (M S ) and the ratio (M S / M T ) is preferably 0.5 or less, more preferably 0.3 or less, even more preferably 0.1 or less, and particularly preferably 0.01 or less. This can further reduce the amount of sulfates that precipitate simultaneously with the positive electrode active material precursor (hydroxide of transition metal). As a result, the amount of sulfates mixed into the positive electrode active material after production can be more suitably reduced. On the other hand, the above M S / M T The lower limit of is not particularly limited, and is 0 or more (M S = 0 mol / L) is also acceptable.

[0028] <Other embodiments> The first embodiment of the technology disclosed herein has been described above. Note that the technology disclosed herein is not limited to the first embodiment described above, and includes other embodiments in which various configurations are modified. Other examples of the embodiment of the technology disclosed herein will be described below.

[0029] (1) Type of starting material In the first embodiment, a used positive electrode active material (LNCM oxide) is used as a NiCo source. In the first embodiment, manganese chloride (MnCl2) is used as a Mn source. However, the manufacturing method disclosed herein is not limited to a form using a specific starting material. For example, nickel oxide, nickel carbonate, nickel acetate, nickel chloride, nickel hydroxide, nickel nitrate, etc. can be used as other examples of the starting material (Ni source) that supplies Ni. In addition, cobalt oxide, cobalt carbonate, cobalt acetate, cobalt chloride, cobalt hydroxide, cobalt nitrate, etc. can be used as other examples of the starting material (Mn source) that supplies Mn. In addition to manganese chloride, manganese oxide, manganese carbonate, manganese acetate, manganese chloride, manganese hydroxide, manganese nitrate, etc. can be used as other examples of the starting material (Mn source) that supplies Mn. These starting materials also do not substantially contain sulfur element, so a transition metal solution with a sulfate ion concentration of 0.9 mol / L or less can be easily prepared.

[0030] Furthermore, the technology disclosed herein does not prohibit the use of sulfates (nickel sulfate, cobalt sulfate, manganese sulfate, etc.) as starting materials. In other words, as long as the sulfate ion concentration of the transition metal solution can be controlled to 0.9 mol / L or less, sulfates may be used as part of the starting materials. For example, if a NiCo source (used positive electrode active material, etc.) that does not substantially contain sulfur elements is used, the inclusion of sulfur elements derived from the supply of Ni and Co can be suppressed. When the positive electrode active material to be manufactured is a low Mn LNCM material, the amount of Mn source added is smaller than that of the NiCo source. In such a case, even if a sulfate (manganese sulfate) is used as the Mn source, the sulfate ion concentration of the transition metal solution can be suppressed to 0.9 mol / L or less.

[0031] (2) Selection of starting materials In the above-described embodiment, a starting material with a known composition is used, and the sulfate ion concentration of the transition metal solution is controlled to 0.9 mol / L or less. However, the manufacturing method disclosed herein can also use a material with an unknown composition (such as a mined mineral or a recycled material of unknown origin) as the starting material. In this case, as shown in FIG. 2, it is preferable to carry out a measurement step S12 and a raw material selection step S14 in the preparation step S10. A specific description will be given below.

[0032] First, in the measurement step S12, the molar concentration of the sulfur element in the starting material is measured. In this step, conventionally known elemental analysis techniques can be used without any particular restrictions. Examples of such elemental analysis techniques include ICP analysis, SEM-EDS analysis, and XRF analysis. Next, in the raw material selection step S14, starting materials in which the molar concentration of the sulfur element is below a predetermined threshold are selected as starting materials to be provided to the preparation step S20. This allows the sulfate ion concentration of the transition metal solution to be sufficiently reduced even when starting materials whose detailed composition is unknown are used. The threshold value set in the raw material selection step S14 can be appropriately set from the viewpoint of suppressing the sulfate ion concentration of the transition metal solution to 0.9 mol / L or less.

[0033] The measurement step S12 and the raw material selection step S14 shown in FIG. 2 may be performed when using starting materials whose compositions are known. This allows the amount of sulfur element mixed into the starting materials as impurities to be grasped, so that the mixing of sulfur element derived from the starting materials can be more suitably suppressed. In addition, the above-mentioned measurement step S12 and raw material selection step S14 do not need to be performed for all starting materials used. For example, the measurement step S12 and raw material selection step S14 may be performed when the type or lot of the starting materials is changed, or when the conditions of other steps are changed. This allows the production of a positive electrode active material with a low amount of sulfate mixed in without significantly reducing the production efficiency.

[0034] (3) Type of extract In the first embodiment, ammonia water is used as an extracting liquid for extracting Ni and Co from the NiCo raw material. Furthermore, water is used as an extracting liquid for extracting Mn from the Mn raw material. However, the extracting liquid used in the preparation step S20 may be selected from conventionally known extracting liquids without any particular limitation as long as it can extract the target transition metal element from the starting material. Other examples of the extracting liquid include organic acids such as citric acid, ascorbic acid, oxalic acid, and acetic acid, and inorganic acids such as nitric acid, hydrochloric acid, phosphoric acid, and sulfuric acid. However, sulfuric acid may cause sulfur elements to be mixed into the transition metal solution. For this reason, when sulfuric acid is used as the extracting liquid, it is necessary to appropriately adjust the concentration of sulfuric acid and the type of starting material so that the sulfate ion concentration of the transition metal solution is 0.9 mol / L or less.

[0035] (4) Separation of elemental sulfur In each of the above-described embodiments, the sulfate ion concentration of the transition metal solution is controlled to 0.9 mol / L or less by suppressing the inclusion of sulfur elements derived from the materials (starting material, extract) of the transition metal solution. However, in the technology disclosed herein, when the precursor generating step S30 is performed, it is sufficient that the sulfate ion concentration of the transition metal solution is controlled to 0.9 mol / L or less. That is, after preparing a transition metal solution having a sulfate ion concentration exceeding 0.9 mol / L in the preparation step S20, sulfate ions may be removed from the transition metal solution. Even when such a form is adopted, it is possible to control the sulfate ion concentration of the transition metal solution to 0.9 mol / L or less and produce a positive electrode active material with a small amount of sulfate salt inclusion. As a specific means for removing sulfate ions from the transition metal solution, calcium hydroxide may be added. This allows sulfate ions to be removed as calcium sulfate.

[0036] (5) Type of positive electrode active material In each of the above-described embodiments, a lithium nickel cobalt manganese composite oxide is produced as a positive electrode active material. However, the technology disclosed herein is not limited by the type of positive electrode active material to be produced. In other words, the production method disclosed herein can also produce other lithium transition metal composite oxides (such as LN oxide, LC oxide, LNM oxide, LMC oxide, and LNC oxide).

[0037] [Test example] Test examples relating to the technology disclosed herein will be described below. Note that the contents of the test examples described below are not intended to limit the technology disclosed herein.

[0038] 1. Sample Preparation In this test, three types of positive electrode active materials with different manufacturing procedures were prepared. The manufacturing procedures for each example are explained below.

[0039] (1) Example 1 In Example 1, transition metal sulfates were prepared as starting materials. Specifically, nickel sulfate hexahydrate (NiSO4·6H2O) was prepared as the Ni source, cobalt sulfate heptahydrate (CoSO4·7H2O) was prepared as the Co source, and manganese sulfate pentahydrate (MnSO4·5H2O) was prepared as the Mn source.

[0040] Next, the above-mentioned transition metal sulfates were dissolved in water to prepare a transition metal solution. At this time, the amount of the starting materials added was adjusted so that the concentration of the transition metal elements in the solution was 1.5 mol / L. The mixing ratio of the Ni source, Co source, and Mn source was adjusted to Ni:Co:Mn=8:1:1.

[0041] Next, a reaction tank containing 0.5 wt% NH3 water was prepared. The temperature of the reaction tank was maintained at 40°C, and while stirring at 600 rpm, the transition metal solution, 28 wt% NH3 water, and 30 wt% NaOH aqueous solution were continuously dropped. The transition metal solution and the NaOH aqueous solution were continuously dropped for 6 hours while adjusting the amount of NaOH aqueous solution added so that the pH in the reaction tank was maintained at 11.4. Then, the solid matter precipitated in the reaction tank was collected by solid-liquid separation. The collected solid matter was washed twice with water and then dried. The NiCoMn hydroxide obtained in this manner was used as a positive electrode active material precursor.

[0042] Next, a mixed material was prepared by mixing the positive electrode active material precursor with lithium hydroxide (LiOH). The mixing ratio of each material was adjusted so that the molar ratio of lithium to transition metal elements was 1.06:1. The mixed material was then subjected to a firing process. The firing process conditions were set as follows: maximum temperature 800°C, firing time 5 hours, and firing atmosphere oxygen atmosphere. In this way, LNCM oxide (positive electrode active material) was produced.

[0043] (2) Example 2 In Example 2, first, the used positive electrode active material (LNCM oxide, Ni:Co:Mn=8:1:1) was calcined (calcination temperature: 650°C, calcination time: 5 hours, calcination atmosphere: oxygen atmosphere). Then, the calcined positive electrode active material was used as a NiCo source. This positive electrode active material was immersed in an NH3 solution to exude NiCo in the positive electrode active material. The NH3 solution used was a mixed solution of 28wt% NH3, 0.5mol / L (NH4)2SO4, and 0.5mol / L H2O2. In the NH3 immersion treatment, the material was immersed in an NH3 solution maintained at a temperature of 80°C for 8 hours while stirring at 500rpm. Then, the solid content was removed by solid-liquid separation to obtain a solution containing Ni and Co (NiCo solution). Next, manganese sulfate pentahydrate (MnSO4·5H2O) was added to this NiCo solution so that the total concentration of the transition metal elements was 1.5 mol / L. This resulted in the preparation of a transition metal solution containing Ni, Co, and Mn. In Example 2, the positive electrode active material precursor was crystallized from the transition metal solution according to the same procedure as in Example 1 above, and then the positive electrode active material precursor was used to produce an LNCM oxide (positive electrode active material).

[0044] (3) Example 3 In Example 3, the calcination treatment and NH3 leaching were performed under the same conditions as in Example 2, except that LiNi composite oxide was used as the used positive electrode active material. This resulted in the extraction of only Ni from the used positive electrode active material. Next, cobalt sulfate heptahydrate (CoSO4·7H2O) and manganese sulfate pentahydrate (MnSO4·5H2O) were added to this Ni solution to prepare a transition metal solution containing Ni, Co, and Mn. Then, in Example 3, the LNCM oxide (positive electrode active material) was produced according to the same procedure as in Example 1.

[0045] 2.Evaluation Test (1) Measurement of sulfur contamination During the preparation of Examples 1 to 3, a portion of the transition metal solution was collected and the amount of elemental sulfur was measured using ICP analysis. The sulfate ion concentration (mol / L) of the transition metal solution was calculated based on the measurement results. In addition, in this test, the amount of sulfate in the LNCM oxide after preparation was also measured. In measuring the amount of sulfate, a solution was prepared by dissolving the LNCM oxide in nitric acid. Then, ICP analysis was performed on this solution to measure the amount of elemental sulfur. The sulfate ion concentration in the positive electrode active material was calculated based on the amount of elemental sulfur obtained by the measurement. The results are shown in Table 1.

[0046] (2) Fabrication of lithium-ion secondary batteries Next, lithium ion secondary batteries were produced using the positive electrode active materials of Examples 1 to 3. First, the positive electrode active material, a conductive material (graphite), a binder (polyvinylidene fluoride powder), and N-methyl-2-pyrrolidone (NMP) were mixed to prepare a positive electrode composite slurry. The mixing ratio of each raw material was set to 1 part by mass of the conductive material and 0.9 parts by mass of the binder relative to the positive electrode active material (100 parts by mass). Next, the positive electrode composite slurry was applied to both sides of a positive electrode current collector (aluminum foil) and dried. Then, the coating film after drying was rolled with a rolling roller. In this way, a positive electrode in which a positive electrode active material layer was formed on both sides of the positive electrode current collector was produced.

[0047] Next, a negative electrode was prepared by forming a negative electrode active material layer on both sides of a negative electrode current collector (copper foil). The negative electrode active material layer was prepared by mixing a negative electrode active material (graphite), a binder (styrene butadiene rubber), and a thickener (carboxymethyl cellulose). The mixing ratio of the negative electrode active material, the binder, and the thickener was set to 98:1:1. In addition, a porous film having a three-layer structure of PP / PE / PP was prepared as a separator. Then, a wound electrode body was prepared using a positive electrode, a negative electrode, and a separator. Then, an electrode terminal was attached to this wound electrode body, and the wound electrode body was housed in an aluminum battery case. Next, a nonaqueous electrolyte was poured into the battery case, and a lithium ion secondary battery for evaluation was prepared. In this test, the non-aqueous electrolyte used was a mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 3:4:3 to which 1.0 mol / L of LiPF6 was added.

[0048] (3) Evaluation of output characteristics The above-mentioned evaluation battery was charged to half of the initial capacity at a constant current of 0.5 It in a temperature environment of 25 ° C. Then, after stopping charging and leaving it for 15 minutes, the voltage was measured when charging at a constant current of 0.1 It for 10 seconds. Next, after discharging the charge capacity for 10 seconds, the voltage was measured when charging for 10 seconds with a different current value. Then, the charge capacity for 10 seconds was discharged. Then, while measuring the voltage, the above-mentioned charge and discharge cycle was repeated at current values ​​from 0.1 It to 2 It. Then, the initial resistance was measured based on the measured voltage and current value. The results are shown in Table 1. In Table 1, the ratio is shown when the initial resistance of Example 1 is 100%.

[0049] [Table 1]

[0050] As shown in Table 1, it was confirmed that the sulfate ion concentration of the transition metal solution was reduced by using LNCM oxide as part of the starting material. It was also found that the amount of sulfate salts mixed into the positive electrode active material could be reduced by controlling the sulfate ion concentration of the transition metal solution to 0.9 mol / L or less. It was also confirmed that a positive electrode active material with a low amount of sulfate salts mixed in could reduce the initial resistance of a lithium-ion secondary battery by 5% or more, as shown in Examples 2 and 3.

[0051] Although the technology disclosed herein has been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes to the specific examples exemplified above. In other words, the technology disclosed herein includes the embodiments described in the following items 1 to 8.

[0052] <Item 1> A preparation step of preparing a starting material containing at least a transition metal element; a preparation step of preparing a transition metal solution by dissolving the transition metal element in the starting material in an extraction liquid; a precursor production step of crystallizing a positive electrode active material precursor by adding an alkaline solution to the transition metal solution; an active material generating step of generating a positive electrode active material by heating the positive electrode active material precursor together with a lithium compound; Including, 4. A method for producing a positive electrode active material, comprising: controlling a sulfate ion concentration of the transition metal solution to 0.9 mol / L or less when carrying out the precursor producing step.

[0053] <Item 2> 2. The method for producing a positive electrode active material according to item 1, wherein the starting material contains at least Ni and / or Co.

[0054] <Item 3> 3. The method for producing a positive electrode active material according to item 1 or 2, wherein the starting material is a positive electrode active material of a used lithium ion secondary battery.

[0055] <Item 4> The preparation step includes: measuring the molar concentration of elemental sulfur in the starting material; a raw material selection step of selecting a starting material having a molar concentration of sulfur element below a predetermined threshold as a starting material to be provided to the preparation step; 4. The method for producing a positive electrode active material according to any one of items 1 to 3, comprising:

[0056] <Item 5> 5. The method for producing a positive electrode active material according to any one of items 1 to 4, wherein the extract is at least one selected from the group consisting of ammonia water, citric acid, ascorbic acid, oxalic acid, acetic acid, nitric acid, hydrochloric acid, phosphoric acid, and sulfuric acid.

Claims

1. A preparation step of preparing a starting material containing at least a transition metal element; a preparation step of preparing a transition metal solution by dissolving the transition metal element in the starting material in an extraction liquid; a precursor production step of crystallizing a positive electrode active material precursor by adding an alkaline solution to the transition metal solution; an active material generating step of generating a positive electrode active material by heating the positive electrode active material precursor together with a lithium compound; Including, The method for producing a positive electrode active material, wherein the sulfate ion concentration of the transition metal solution during the precursor production step is set to 0.9 mol / L or less.

2. The method for producing a positive electrode active material according to claim 1 , wherein the starting material contains at least Ni and / or Co.

3. The method for producing a positive electrode active material according to claim 2 , wherein the starting material is a positive electrode active material of a used lithium ion secondary battery.

4. The preparation step includes: measuring the molar concentration of elemental sulfur in the starting material; a raw material selection step of selecting a starting material having a molar concentration of sulfur element below a predetermined threshold as a starting material to be provided to the preparation step; The method for producing a positive electrode active material according to claim 1 ,

5. The method for producing a positive electrode active material according to any one of claims 1 to 4, wherein the extract is at least one selected from the group consisting of ammonia water, citric acid, ascorbic acid, oxalic acid, acetic acid, nitric acid, hydrochloric acid, phosphoric acid, and sulfuric acid.

Citation Information

Patent Citations

  • Recovery of valuable metal from active material of positive electrode for lithium ion secondary battery

    JP1998287864A

  • Production of nickel-containing hydroxide

    JP1999130440A

  • Preparation of lithium manganate compound for lithium ion secondary battery

    JP1999233112A

  • Tricobalt tetroxide and its production

    JP1999292548A

  • Lithium secondary battery

    JP2004006247A